Validation of “creactability” scale in football: a Rasch modeling approach - Jhinyi Shin; Jongwon Kim; Miyoung Lee; Won Jae Lee (Frontiers in Sports and Active Living)
PurposeThe aim of this study was to investigate the construct-related validity evidence of the “creactability” scale, developed for athletes in the sports field, using the Rasch model. The specific aims were (1) each scale measures a unidimensional construct, (2) the scale items investigate the Differential Item Functioning (DIF) base on team group (i.e., the rankings of higher and lower teams), (3) the range of “creactability” item difficulty and personal ability (respondents “creactability” levels) are wide enough to assess the “creactability” changes, and (4) “creactability” differs across subscales (7 points).MethodsFor Rasch analysis, data from a total of 241 football players were used from the K-League (Korean Professional Football League), excluding goalkeepers due to their different abilities and roles from other field players. The coaches from 7 teams evaluated their players (34.4 players on average per team). The “creactability” scale included a total of 9 items, consisting of 3 items each for subfactors (i.e., quickness, creativity, and adaptability) with a 7-point Likert scale. The Rasch model was applied using WINSTEPS Version 5.7.4 and FACETS Version 4.1.8.ResultsThe results (1) Confirmed the unidimensionality of all 9 items, as their infit and outfit values fell within the range of 0.7–1.3. (2) None of the items in the position scales showed statistically significant DIF (p > 0.05). (3) The Person Separation Index (PSI) criterion value for the “creactability” scale of football players is 4, which was within a range of 0–7 point. (4) All subscales demonstrated good-fit in both infit and outfit, ranging between 0.69 and 1.28, respectively. The response rate for scales 4–5–6 point was 68%, and the outfit for respondents across all scales were satisfactory at 1.30 or lower.ConclusionPhysical activity (PA) should be maintained or increased, particularly in the context of social distancing measures during the pandemic. To ensure that PA can be sustained, a program should be developed that considers the individual's geographical location, economic status, lifestyle, and environment.